Implementasi Dalam Pelatihan Bahasa Inggris Di LKP Deas Intenational College - Irwan Dwi Oktovi Asri; Ebok .; Safira Oktaviana; Sekar Nadya Putri (CV. ITTC INDONESIA, 2023)
This English language training program is implemented at lkp Deas International Serang City with the aim of improving English language skills. this research program aims to find out the goal-free evaluation: implementation in English language training at lkp deas international college. The purpose of this research is to find out the goal-free evaluation system in the Deas International English training program besides that this research aims to find out the mastery of linguistic abilities, namely English, the ability to master vocabulary and grammar, comfort and confidence in communicating using English and public speaking skills using English in English language training program participants at Deas International College. This study uses a qualitative research method where researchers analyze the problem and then look at the results of the objectives of the training program being studied. The data collection method used interviews and observation. The conclusion of this study is that these English training programs have a positive impact on participants in improving English language skills, English speaking skills, vocabulary mastery and self-confidence, because it follows the needs of society which requires many skills and certificates for job requirements.